Towards a comprehensive system for the recognition of double helical DNA : components for T and A - Dunne, Gavin Patrick (Trinity College (Dublin, Ireland). School of Chemistry, 2000)
This thesis gives an account of the attempted synthesis of sequence selective double stranded DNA ligands. Two distinctive ligands types were envisaged, a pyrrolo[2', 3': 4, 5] thieno [2, 3-d]imidazole system (1.40 and 1.41) for the binding to the T-A/A-T base pairs, and an N-carbamoyl squaramide system (1.44) for binding the G-C/C-G base pairs.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin